2000
DOI: 10.1145/345063.339342
|View full text |Cite
|
Sign up to set email alerts
|

On achievable service differentiation with token bucket marking for TCP

Abstract: The Differentiated services (diffserv) architecture has been proposed as a scalable solution for providing service differentiation among flows without any per-flow buffer management inside the core of the network. It has been advocated that it is feasible to provide service differentiation among a set of flows by choosing an appropriate “marking profile” for each flow. In this paper, we examine (i) whether it is possible to provide service differentiation among a set of TCP flows by choosing appropriate markin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Sahu et al [135] determine the parameters of a leaky-bucket marking necessary for guaranteeing a given rate, if at all possible. They reach similar conclusions as above such as that in the under-subscribed case, when the committed rate is small, the marking has no influence on the achieved rate.…”
Section: Providing Service Guarantees With Tcp Flowsmentioning
confidence: 99%
“…Sahu et al [135] determine the parameters of a leaky-bucket marking necessary for guaranteeing a given rate, if at all possible. They reach similar conclusions as above such as that in the under-subscribed case, when the committed rate is small, the marking has no influence on the achieved rate.…”
Section: Providing Service Guarantees With Tcp Flowsmentioning
confidence: 99%
“…With rigorous simulations we show that our scheme converges to the optimal bucket size in most cases and this is achieved without any knowledge of parameters such as round trip time or level of aggregation of the tra¢ c being policed. Although TCP's interaction with a token bucket policer has been widely studied ( [70], [12], [40], [90]), the previous work has not achieved the con…guration of token bucket parameters independent of the tra¢ c pro…le.…”
Section: Chapter 4 a Dynamic Token Bucket Policermentioning
confidence: 99%
“…It has been seen throughout a number of studies [e.g. 4,5,6,7,8] that it is difficult to guarantee requested throughput to the TCP flows in a such network. Most of these studies have concluded that the throughput attained by a customer is affected, not only by the marking strategies at the edge router, but by the presence of other flows in the same bottleneck link.…”
Section: Introductionmentioning
confidence: 99%
“…Sahu et al in [5] derived a simple analytical model for determining the achieved rate of a TCP flow when edge routers use token bucket marking and the core routers use active queue management for preferential packet dropping. As shown in [5], it is not feasible to achieve ideal service differentiation across a set of TCP with token bucket marking. In their study, they focused on a single TCP flow, i.e.…”
Section: Introductionmentioning
confidence: 99%